Diet as a risk factor for antimicrobial resistance in community-acquired urinary tract infections in a middle-aged and elderly population: a case–control study. (May 2019) - Mulder, M.; Kiefte-de Jong, J.C.; Goessens, W.H.F.; de Visser, H.; Ikram, M.A.; Verbon, A.; Stricker, B.H.
Abstract: Objectives: There is an ongoing debate as to what extent antimicrobial resistance (AMR) can be transmitted from animals to humans via the consumption of animal products. Because epidemiological data on the role of diet in AMR in humans are lacking, we investigated this association between diet and AMR for different antimicrobial drugs in Escherichia coli (E. coli) in urinary tract infections (UTIs). Methods: Susceptibility of E. coli in urinary cultures and information on diet (with food frequency questionnaires) were obtained from participants of the Rotterdam study, a population-based prospective cohort study. The association between intake of several food groups (meat, seafood, eggs, dairy products, crops) and resistance of E. coli to several antimicrobial drugs (amoxicillin, amoxicillin-clavulanic acid, trimethoprim, sulfamethoxazole-trimethoprim, first-generation cephalosporins, cefotaxime, nitrofurantoin, norfloxacin) was studied. Results: Urinary cultures with E. coli were obtained from 612 individuals, of whom 481 (78.6%) were women. Resistance rates varied from 246/611 (40.3%) for amoxicillin and 167/612 (27.3%) for trimethoprim to only 29/612 (4.7%) for nitrofurantoin and 16/462 (3.5%) for cefotaxime. A higher intake of chicken was associated with cefotaxime resistance (OR 2.18; 95% CI 1.05–4.51 per tertile increase); a higher intake of pork was associated with norfloxacin resistance (OR 1.42; 95% CI 1.04–1.95 per quartile increase). In contrast, a higher intake of cheese was associated with lower AMR to amoxicillin (OR 0.84; 95% CI 0.72–0.99 per quartile increase) and amoxicillin-clavulanic acid (OR 0.67; 95% CI 0.53–0.86 per quartile increase). Conclusions: These findings support the hypothesis that diet may play a role in the AMR of E. coli in UTIs.